Бактериска вагиноза и матернални серумски метаболити на азотен оксид во корелација со предвремено породување - Стојовска Лазарова, Александра (Медицински факултет, УКИМ, Скопје, 2019)
Introduction: Preterm birth (PB) continues to be one of the most challenging problems in perinatology. It defines as a birth between 22 and 37 gestational weeks (1). The number of preterm born fetuses rises every year and the rate is between 5-10 % globally. Early preterm birth (the one that occurs before 28-th gestational weeks) is commonly related to increased perinatal morbidity and mortality. Due to the intensive efforts and researches in this field, modern medicine can’t do much progress to lower the rate of PB. Clinical and experimental studies show that infection, mainly subclinical, plays an important and crucial role in his appearance and is one of the risk factors for neonatal outcome. Goal: The main goal is to determine and to show that ascending bacterial vaginosis plays an important role in preterm birth and to see the predicitive value of maternal metabolites of nitric oxide concentration. Materials and methods: In this prospective study 130 pregnant women with singleton pregnancies were enrolled. The study groups were devided in two categories: study group, which was subdevided in: subgroup А, patients who had preterm birth and subgroup B, patients who had administered tocolytic therapy after which the pregnancy continued and control group, patients delivering in term (37-41.6 gestational age). All of the participants were hospitalized on University Clinic of gynecology and obstetrics. The women enrolled in the study had additional investigations. The concentration of nitric oxide in maternal serum was determined with Nitric oxide multispecies Elisa kit. Every woman had signed informed consent before any investigation done. Results: When we compared the predictive value for PP in women who have BV compared to those who haven’t BV the preterm birth risk was 5,42 and those are with greater probability for PB wih CI of 95%. ROC area was 0.667 or 66,70% higher accuracy for PB. Elevated vaginal pH>4,5 is a good predictor for PB and the same result was confirmed in this study. In our analysis we confirmed that with Kruskal-Wallis ANOVA test(p<0.001) and there is a significant statistical difference between the three groups. The results of the study found that Ureaplasma urealyticum was most common found in the patients and those women who are positive for this bacteria are 4,72 times more likely to have PB compared with those who have negative smear. Mycoplasma hominis, on the other hand as the most common found anaerob and presence of this infect rises the possibility 2,21 times for having PB. The cervical length in the first, control group varies in interval between 15,24±3,32, in the second group in interval between 15,63±4,34 and in third group in interval between 19,79±6,37, which is statistically significant (p<0.001) between the women who had delivered in both groups and those with prolonged pregnanacy. Another parameter where we had significant difference was CRP, between the patients with PB and those were pregnancy continued. In the first group of patients in 20(40,80%) women was found elevated CRP and in the second group 17(33,40%) were with elevated levels of the protein. The most important risk factor, previously preterm birth (PPB) was confirmed in this thesis. In the first group 5 patients have had PB, in the second group there were 18 patients with PPB and in the third 7 patients have had PPB.There is a significant difference between the groups of patients. The weight of the newborns was, as expected, higher in the control group then the group with PB. The average weight of the fetuses in the first group was 3114 gr, in the second group was 1823 gr. and in the third group was 2047 gr. There is significance in the nitrites, which are metabolites of nitric oxide production, between the group where the pregnancy continued (they were much higher) and the other two groups. So, we can tell that their production is crucial for maintaining the pregnancy and their concentrations are lower before birth. BMI, compared with other risk factors is the only one who showed statistical significance between the preterm birth group and the control group. From this results we can conclude that the best prediction model for PB is with determining Vaginal pH, nitric –oxide metabolites, BMI and cervical length.
Докторска дисертација одбранета во 2019 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Никола Пановски.
Keywords: vaginal pH, bacterial vaginosis, cervical length, nitric oxide metabolites, CRP, risk factor